(untitled) - June Jamrich Parsons (Cambridge, MA, 2001)
Microsoft approved study guide for the Microsoft Office Specialist certification program (Excel 2000 expert level). Covers the basic to more advanced features of Excel 2000 from creating, editing, and formatting a document, to customizing Excel and integrating it with other programs
Keywords: Business; Electronic spreadsheets; Microsoft Excel (Computer file)